Faktor-Faktor Yang Menyebabkan Terjadinya Penurunan Minat Masuk Perguruan Tinggi Bagi Siswa Lulusan Sekolah Menengah Tingkat Atas di Daerah Istimewa Aceh - T.M. Jamil; Mahyudin S. Anwar Hanafiah (Universitas Negeri Malang, 2016)
The causal factors of the decrease in enrollment at the higher education in the province of Aceh is under investigation. Employing the puposive random sampling technique, 200 graduates of 1991 and 1992 of the general secondary schools who did not further their study are the object of this research. It was disclosed that the most dominant factor influencing the number of students continuing to the tertiary education was a matter of finance.